For Better, For Worse: Intrahousehold Risk-Sharing over the Business Cycle - Shore, Stephen H (The Review of Economics and Statistics, 2010)
Marriage allows couples to diversify labor income risks and dynamically coordinate labor supply decisions in response to shocks. This paper argues that these risk-sharing benefits of marriage are countercyclical; husbands' and wives' income changes are more positively correlated when the economy is growing rapidly. As a result, while individuals face more idiosyncratic income risk in bad times than in good, households do not. I exploit variation in the cross-sectional covariance of husbands' and wives' incomes to infer the covariance of past income changes. Couples with marriages spanning periods of greater economic expansion have more positively correlated incomes in the cross-section.